Understanding girls' problem behavior : how girls' delinquency develops in the context of maturity and health, co-occurring problems, and relationships - Kerr, Margaret, 1953-; Wiley InterScience (Online service) (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2011)
Understanding Girls' Problem Behavior presents an overview of recent studies by leading researchers into key aspects of the development of problem behavior in girls.: Integrates interdisciplinary research into girls' problem behaviors (e.g. aggression, antisocial behavior, rule breaking); Unique in seeking to understand girls' problem behaviors in their own right; Follows the maturing girl from adolescence to adulthood, concluding at the point where she herself becomes a parent and forms new relationships; Gives attention to the critical contexts of problem behavior development--society and nei.
Girls' problem behavior : from the what to the why / Geertjan Overbeek & Anna-Karin Andershed -- A contextual amplification hypothesis : pubertal timing and girls' emotional and behavioral problems / Xiaojia Ge [and others] -- Fits and misfits : how adolescents' representations of maturity relate to their adjustment / Lauree C. Tilton-Weaver [and others] -- Physical health in adolescent girls with antisocial behavior / Kathleen Pajer, Andrea Lourie & Lisa Leininger -- Using girls' voices and words to study their problems / Joanne Belknap [and others] -- Developmental comorbidity of depression and conduct problems in girls / Kate Keenan [and others] -- Deviancy training in a sample of high-risk adolescent girls in the Netherlands / Annika K.E. de Haan [and others] -- Girls' aggressive behavior problems : a focus on relationships / Debra Pepler [and others] -- Attachment and aggression : from paradox to principles of intervention to reduce risk of violence in teens / Marlene M. Moretti & Ingrid Obsuth -- The transfer of developmental and health risk from women with histories of aggressive behavior to their children : recent results from the Concordia Longitudinal Project / Lisa A. Serbin [and others].
Includes bibliographical references and index.
Print version record.
Keywords: Behavior disorders in children; Behavior disorders in adolescence; Problem children -- Mental health; Problem youth -- Mental health; Girls -- Mental health; Teenage girls -- Mental health; Juvenile delinquency -- Etiology; Juvenile Delinquency; Adolescent Behavior; Adolescent Development; Aggression; Conduct Disorder; Psychology; MEDICAL -- Psychiatry -- Child & Adolescent; Electronic books